Perancangan Spin Coater Menggunakan Motor DC Brushless Dari Hardisk Bekas - Firmansyah, Firmansyah; Deswita, Pipi (Universitas Islam Negeri Imam Bonjol Padang, 2021)
The building ofÂ low voltage and cost of spin coater using DC brushless motor from the old hard disk drivers has been carried out. The spin speed of spin coater offers manual control using potensiometer. The equipment consist of the simple hardware: IC timer 555, IC shift register SIPO 74LS164, IC driver L293D, microcontroller AT889S52, LCD and then motor speed detector using a couple of photodiode and LED and using IC Schmitt trigger inverter 74LS14 as the amplifier of the sensor. The data analysis result showed that the speed up spin ofÂ the spin coater depend on the signal frequency from multivibrator. The equipment has spin speed stability with speed range from 180 rpm until 2460 rpm. Spin coater to be tested for applications where a glass slide microscope are coated with TiO2 (Titanium Dioksida) about varies speed and show that coating result can be fliemsier with addition of speed spin the spin coater.